The Relation Between Serum Levels of Insulin-like Growth Factor-1 and Bronchopulmonary Dysplasia - Nükhet Aladağ Çiftdemir; Betul Acunas; Ülfet Vatansever Özbek; Rıdvan Duran (Galenos Publishing House, 2019)
INTRODUCTION: Bronchopulmonary dysplasia (BPD) is the most important consequence of premature delivery at long term which remains obscure. Insulin-like growth factor-1 (IGF-1) is involved in both prenatal and postanatal lung growth. Our aim is to characterize postanatal changes in serum IGF-1 in relation to development of BPD in preterms. METHODS: 67 preterm newborns were recruited prospectively to our study in order to investigate independent risk factors associated with BPD and to determine the relation between serum IGF-1 levels and BPD. Infants who developed BPD were designated as Group 1 (n=12) and those who did not as Group 2 (n=55). Serum IGF-1 levels were measured from venous blood samples of each infant on days 1, 7, 14 and 28 after birth. RESULTS: Chorioamnionitis increased the risk of the development of BPD by 12.3 fold, antenatal bleeding by 6.3 fold, vaginal delivery by 89.3 fold, respiratory distress syndrome by 15.3 fold, and postnatal sepsis by 28.7 fold. However administration of antenatal steroid significantly reduced (odds ratio; 20) the development of BPD. The serum IGF-1 levels of infants in Group 1 on day 1 samples was higher than those in Group 2 with borderline significance. The sensitivity and specificity of day 1 and day 7 serum IGF-1 levels were found to be low in predicting the development of BPD. DISCUSSION AND CONCLUSION: We could not find any relation between BPD and serum IGF-1 levels in our study and concluded that the low number of newborn with BPD could have limited the evaluation of this association.